PENGARUH LEVERAGE, TRANSFER PRICING TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DALAM BEI PADA TAHUN 2020-2022 - Manullang, Martha; Karundeng, Meidy Lieke (FEB Universitas Sam Ratulangi Manado, 2023)
Many companies try to optimize their business profits by reducing the tax obligations they have to pay. In this research, the author tries to examine technology sector companies listed on the IDX in 2020-2022 to determine the effect of leverage and transfer pricing on tax aggressiveness. By using the purposive sampling method, a sample size of 15 companies was obtained, and the results of the SPSS version 29 test showed that partially, the leverage variable on tax aggressiveness had a negative and insignificant effect (0.882 > 0.05) and the transfer pricing variable on tax aggressiveness had a negative and insignificant effect. not significant (0.537 > 0.05).